A chromosome-level genome assembly of Chinese quince (Pseudocydonia sinensis) - Yang, Ying; Liu, Jin Feng; Jiang, Xian Feng (Frontiers in Plant Science, 2024)
Introduction Pseudocydonia sinensis, also known as Chinese quince, is a perennial shrub or small tree highly valued for its edibility and medicinal properties. Method This study presents the first chromosome-level genome assembly of P. sinensis, achieved using HiFi sequencing and Hi-C scaffolding technology. Results The assembly resulted in a high-quality genome of 576.39 Mb in size. The genome was anchored to 17 pseudo-chromosomes, with a contig N50 of 27.6 Mb and a scaffold N50 of 33.8 Mb. Comprehensive assessment using BUSCO, CEGMA and BWA tools indicates the high completeness and accuracy of the genome assembly. Our analysis identified 116 species-specific genes, 1196 expanded genes and 1109 contracted genes. Additionally, the distribution of 4DTv values suggests that the most recent duplication event occurred before the divergence of P. sinensis from both Chaenomeles pinnatifida and Pyrus pyrifolia. Discussion The assembly of this high-quality genome provides a valuable platform for the genetic breeding and cultivation of P. sinensis, as well as for the comparison of the genetic complexity of P. sinensis with other important crops in the Rosaceae family.